Malignant proliferating trichilemmal tumor of thigh: a case report of an unusual location of a rare cutaneous adnexal tumor - Mohanan, Athira (International Surgery Journal, 2022)
Proliferating trichilemmal tumour (PTT) is a well-circumscribed dermal or subcutaneous neoplasm with squamoid cytologic features and trichilemmal-type of keratinization. Usually, proliferating trichilemmal cysts are benign, although rarely, can undergo malignant transformation, at which point they are referred to as malignant proliferating trichilemmal tumours (MPTTs). Ninety percent of PTTs occur on the scalp, but they have also been found on the forehead, nose, back, chest, abdomen, buttocks, elbow, wrist, mons pubis and vulva. Here a case of an 89-year-old woman with a malignant proliferating trichilemmal tumour of right thigh is discussed, which is a very rare site for occurrence of the same.